Propidium monoazide-quantitative PCR to detect viable Legionella spp. in the supply process of tap water. Issue 7 (22nd June 2022) - Lee, Eun-Sook; Han, Ji-Sun
Abstract: Legionella are common in the aquatic environment and are responsible for legionellosis including severe pneumonia and Pontiac fever. The culture method has some limitations in quickly detecting viable Legionella . Therefore, we optimized real-time PCR (qPCR) combined with propidium monoazide (PMA) to quantify viable Legionella in the supply process of tap water, considering factors such as PMA concentration, length of the target gene, and turbidity of water samples. Among 30, 50, 100, and 200 μM PMA concentration, 100 μM PMA had the greatest difference in copy number between PMA-treated live and dead cells while minimizing the cytotoxic effect on live cells. Among the various sizes of the target gene (108, 386, 456, and 654 bp), the primer in 386 bp size effectively excluded dead cells without loss of qPCR efficiency. As a result of applying the PMA-qPCR method to samples including river, purified water, and tap water, live and dead cells could be distinguished for samples with turbidity of less than 10 NTU. The optimized PMA-qPCR can be a useful method of rapidly detecting viable Legionella spp. in the process of supplying tap water, and contributing to tap water that is safe from pathogens. HIGHLIGHTS: The PMA-qPCR method was optimized to monitor rapidly viable Legionella in the supply process of tap water. The PMA concentration and target gene size were major factors to exclude dead cells without affecting live cells. The PMA-qPCR was efficient in water samples with turbidity of less than 10 NTU.